If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 3(x + 1) + 3x Reorder the terms: -5 + 6x = 3(x + 1) + 3x Reorder the terms: -5 + 6x = 3(1 + x) + 3x -5 + 6x = (1 * 3 + x * 3) + 3x -5 + 6x = (3 + 3x) + 3x Combine like terms: 3x + 3x = 6x -5 + 6x = 3 + 6x Add '-6x' to each side of the equation. -5 + 6x + -6x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + 0 = 3 + 6x + -6x -5 = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 = 3 + 0 -5 = 3 Solving -5 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6(3x-6)=24 | | a=1/2(b1+b2)h | | 64^1/3 | | x^2-3/4x-7/64=0 | | 25+2x-6=11x-9-5x | | 57=y | | 57=x | | 8y/3=24 | | .05x+.07(x+2000)=1220 | | 3c=9 | | 7(8x-2)=14 | | 0.03x=2+0.015x | | a=b+20 | | x-7.2=2 | | Y=(x+2)(x-6) | | 5x+3-8x=-12 | | b=a+20 | | Y=x^2+-14x+35 | | 2x-12-9x=18-18x+11x-6 | | 2.25x-0.125=3x+3175 | | 40x+5y=15 | | 9=10+h | | 5m+10n=40 | | 4(x-3)+5(x-3)=8x+10 | | x+2(x+6)=36 | | 4(4+x)=3(x-1) | | 5x+20=4(2x-1) | | (2y+1)22= | | -3n+6=0 | | 2(x+14)=-3x-7 | | 04x+2=10 | | 12s-11=11s+4 |